Stereoselective synthesis of perhydrobenzo[4.5.6]cholestanes - Borry, Joost (Department of Chemistry, 2016)
An intramolecular Michael-aldol reaction sequence has been developed for the stereocontrolled synthesis of pentacyclic steroids! with the new six-membered ring attached to the C(4) and C(6) positions. Cholesterol was converted into 3β-hydroxycholest-4-en-6-one by standard methods, and the corresponding 3α-isomer was obtained through Mitsunobu inversion. Acetoacetylation of the 3-alcohols afforded the corresponding 3β- and 3α-acetoacetoxycholest-4-en-6-ones, which served as substrates for an investigation of intramolecular condensation routes to the target ring systems. Base treatment of the 3β-ester resulted in an efficient and stereocontrolled intramolecular Michael addition to give (2R)-2-(3β-hydroxy- 6-oxo-5β-cholestan-4β-yl)-3-oxobutanoic acid 1,3'-lactone, and reaction conditions were developed to achieve sequential lactone cleavage, decarboxylation, and aldol closure, leading to 3β,6-dihydroxy- 4α,4',5β,6β-tetrahydrobenzo[4.5.6]cholestan-5'(6'H)-one. Although this product resisted base-mediated B-elimination, acid treatment resulted in dehydration to give the corresponding Δ⁶-compound. which underwent double bond isomerisation and 5-epimerisation. to give 3β-hydroxy- 4α,5α-dihydrobenzo[4.5.6]cholestan-5'(6'H)-one. A similar series of reactions was performed on the 3α-acetoacetate, leading finally to formation of 3α-hydroxy-4β,5α-dihydrobenzo[4.5.6]cholestan-5'(6'H)-one. Modification of foregoing reaction conditions, resulted in the design of a tandem Michael-aldol sequence, in which the 3-acetoacetates could be converted directly into the corresponding pentacyclic enones. These products were interrelated via base-mediated equ1llbration of their respective 3,6-diketones, leading to the thermodynamically favoured 4β,5α-isomer. Preliminary investigations into the stereoselective reduction of the olefinic bond in the 4α.5α-isomer, resulted in the formation of a new class of. hexahydrobenzo[4.5.6]cholestane derivatives. The structural and conformational properties of the condensation products were studied with the aid of ¹H NMR, ¹³C NMR, and IR spectroscopy.